Chemical Vapor Deposition: An Eco‐Friendly, CMOS‐Compatible Transfer Process for Large‐Scale CVD‐Graphene (Adv. Mater. Interfaces 13/2019). Issue 13 (9th July 2019) - Moon, Ji‐Yun; Kim, Seung‐Il; Son, Seok‐Kyun; Kang, Seog‐Gyun; Lim, Jae‐Young; Lee, Dong Kyu; Ahn, Byungmin; Whang, Dongmok; Yu, Hak Ki; Lee, Jae‐Hyun
Abstract : In article number1900084, Ji‐Yun Moon, Dongmok Whang, Hak Ki Yu, Jae‐Hyun Lee, and co‐workers demonstrate a clean transfer method for large scale chemical vapor deposition (CVD) graphene using MoO3 as a protective film, which can be dissolved in pure DI water, easily and completely. The authors believe that this approach provides new solutions to overcome the limitations of the conventional transfer methods for CVD graphene and pave the way for future transfer method for CMOS manufacturing processes.